Factors associated with knowledge, attitude, practice and perception in flood disaster management among critical care nurses in the east coast hospitals of Malaysia - Ismail, Siti Aminah (2020)
The east coast hospitals of Malaysia were regularly stricken by flood disaster, whereby critical care nurses make up the majority of frontline responders in such disaster. They have their roles especially in triage and evacuation of the critically ill patient during a disaster. The general objective of this study was to identify the factors associated with knowledge, attitude, practice, and perception in flood disaster management among critical care nurses in the east coast hospitals of Malaysia. This was a quantitative study with a descriptive cross-sectional study design in, which the data were collected from 250 critical care nurses of the east coast hospitals in Malaysia by using a questionnaire. Multiple logistic regression analysis was used to determine the factors associated with knowledge, attitude, practice, and perception in flood disaster management. A majority of the critical care nurses had adequate knowledge and practice, with a positive attitude and were well-perceived on flood disaster management. Among the selected factors studied, the workplace was significantly associated with knowledge scores (AOR 0.185, 95% CI: 0.049, 0.703, p = 0.013). Disaster response experience had a significant association with knowledge (AOR 4.048, 95% CI: 1.346, 12.174, p = 0.013) and practice (AOR 2.697, 95% CI: 1.122, 6.479, p = 0.027) but no significant association with attitude and perception. Attended disaster training/education had significant association with attitude (AOR 4.230, 95% CI: 1.474, 12.144, p= 0.007) and practice (AOR 4.203, 95% CI: 2.102, 8.402, p =0.000). Level of education and years of service both showed no significant association with knowledge, attitude, practice, and perception. This study revealed that previous disaster response experience and disaster training/education as some of the factors that would ensure adequate knowledge and practice in flood disaster management among critical care nurses. Therefore, it is recommended for disaster management programme to be included in continuing education programme and training for critical care nurses so as to ensure them to be well-prepared and respond competently when flood disasters happen.